(3JfejI GdeHjYGJ GdSjGMjI (B:s (3GSJQGJjLjI GdJejR GdeGdj hGdeMGSHj (B/s - (3MSjf, MSGe GdOjfs ((3GdGScfOQjI(B: s (3ecJHI fGfSj OejGW(B, s, 2007)
(3jVe eGgjI GdeHjYGJ GdSjGMjI, OhQ GdJQhjL GdSjGMj aj JfejI GdeHjYGJ GdSjGMjI, CKQ GdJNWjW GdSjGMj aj JfejI GdeHjYGJ GdSjGMjI, OhQ GdOhdI GdeSGYO ddefTBJ GdSjGMjI aj JfejI GdeHjYGJ GdSjGMjI, OhQ GdEYdGe GdSjGMj aj JfejI GdeHjYGJ GdSjGMjI, GdJShjb ef NdGd QZHGJ GdSGFMjf dJfejI GdeHjYGJ GdSjGMjIs
(3GbJfGAGJ (B2014 3(3f HjHdjhZQGajG(B: (3U U(B.280-285s
Keywords: (3GdSjGMI(B- (3GbJUGOjGJs; (3GdafGOb(B- (3eMGSHIs; (3GdeHjYGJs